Social Semiotic Analysis of a Pet Protection Post on Instagram - Deng, Yaling; Li, Shu; Lu, Biner (International Journal of Social Sciences and Public Administration, 2024)
This study applies Kress and Van Leeuwen's Visual Grammar framework to analyze an Instagram post advocating pet protection. The research focuses on representational, interactive, and compositional metafunctions to understand how visual and textual elements combine to convey urgency and empathy. The representational analysis highlights the dog's isolated portrayal and the use of the pronoun "me" to foster an emotional connection. The interactive analysis examines indirect gaze, close-up shots, and low angles to engage viewers and emphasize their role in pet protection. The compositional analysis reveals the strategic placement of verbal and visual elements, with bold text and contrasting colors enhancing the message's salience. This multimodal approach demonstrates the synergy between visual and textual elements, creating a cohesive and persuasive narrative. The study's findings align with existing literature on social semiotics and Visual Grammar, emphasizing the importance of integrated visual strategies in social media advocacy. The research offers practical insights for designing effective pet protection campaigns, highlighting the role of Visual Grammar in promoting responsible pet ownership and animal welfare. Future research should explore the long-term impact of these visual strategies on viewer behavior and the effectiveness of different semiotic modes across various social media platforms.